Tumor extracellular pH-sensitive polymeric nanocarrier-grafted platinum(iv) prodrugs for improved intracellular delivery and cytosolic reductive-triggered release. Issue 12 (26th February 2020) - Chen, Sheng-Qi; Song, Gang; He, Chen; Hou, Mei; He, Wei-Dong; Li, Hui-Juan; Haleem, Abdul; Li, Qing-Lin; Hu, Rong-Feng
Abstract : Extracellular pH-sensitive Pt(iv )-based nanodrugs enable preferential toxicity to tumor cells via a selectively endocytosed and triggered drug release strategy. Abstract : Platinum drugs have emerged as the most active anticancer agents in clinical tumor treatment. Although platinum drugs are typically effective, they induce severe systemic toxicity due to the lack of selective toxicity and targeting ability between cancer and normal cells. Here, we report an approach to develop tumor extracellular pH-sensitive nanoparticle (esNP)-loaded Pt(iv ) prodrugs (esNP-Pt) having acid-cleavable amide linkages of 2, 3-dimethyl maleamidic acid (DMMA) pendants and GSH-cleavable Pt(iv ) pendants in micellar shells, thus attaining dual-stimuli responses at two locations. These DMMA pendants could achieve charge reversal for specific cellular uptake and endosomal/lysosomal escape via cleaving their amide linkages at pH ≤ 6.8. Cellular uptake assays showed that esNP exhibited similar cellular uptake to pH-insensitive nanoparticles (isNP) with succinamic acid (SA) pendants at pH 7.4, while they showed 6-fold cellular uptake as isNP at pH 6.8 and 10-fold cellular uptake as esNP at pH 7.4. The loaded Pt(iv ) pendants could be reduced and liberate cisplatin. The release rate and the total amount of cisplatin increased 6-fold under the stimuli of 10 mmol GSH. MTT assays demonstrated that esNP-Pt showed preferential inhibition (∼50% inhibition at pH 6.8 against ∼20% inhibition at pH 7.4), indicating preferential toxicity against tumors and weak systemic toxicity. These esNP-Pt possess many favorable traits for preferential toxicity to cancer cells, such as minimized nonspecific uptake in blood circulation, enhanced cellular uptake at the tumor site in response to the tumor extracellular level of pH, improved intracellular drug delivery to the tumor cell cytoplasm (TCC) and the in situ release of cisplatin in response to TCC reductive potential, which make them promising candidates for cancer therapy.